Biotherapeutic Activity of Boerhaavia diffusa against Oxidized Cholesterol Induced Lipid Peroxidation and Anti-Oxidant Status in Hypercholesterolemic Rats - Singh, Puneet Kumar; Ojha, Sanjay Kumar; Mishra, Snehasish; Kumar, Satish; Khan, Amir; Chauhan, Subodh Kumar (International Journal of Applied Sciences and Biotechnology, 2014)
Present days, herbal medicines are widely practiced to treat cardio vascular diseases (CVD) and heart care management in most of the Asian countries. The present study was to evaluate the hypercholesterolemic and antioxidative effect of Boerhaavia diffusa root extract (BD) on oxidized cholesterol induced hypercholesterolemia in rats. The root extract was prepared in 70% ethanolic medium by soxhlet extraction procedure. Experiment was designed to carry out with 18 male albino rats which are equally divided into 3 groups for four week experiment. All experimental animals provided rat chow and water ad libitum. Group II and III received oxidized cholesterol through gastric intubation at the dose of 1mg/rat/day, where as in group III followed by BD at the dose of 1ml/rat/day for 4 weeks. Parameters like lipid peroxidation, total cholesterol and antioxidant status in plasma along with catalase (CAT), glutathione reductase (Gred) and superoxide dismutase (SOD) in liver tissue were analyzed on oxidized cholesterol supplemented rats with and/or without treatment of BD. The total cholesterol (TC), triglycerides (TG) and LDL levels in plasma of group II remained high compared to the counterparts. But in group III showed significant decrease in TC, TG and LDL levels by 34.39%, 42.13% and 48.30%, respectively. The based on findings, it seems very levelheaded to believe that this greener way of formulation of herbal medicines is not just a utilization of naturally occurring medicinal herbs but also to make it available for the betterment of the society at low cost. DOI: http://dx.doi.org/10.3126/ijasbt.v2i1.9483 Int J Appl Sci Biotechnol, Vol. 2(1): 69-74